Overload, Stress, and Satisfaction: Does It Impact Auditor's Intentions to Resign? - Ananta Wahyu Sasongko; Farhani Kautsar Nugraha; Putriana Sriwijianingsih (JAFFA, 2023)
The study aimed to investigate the impact of work overload, work-related stress, and job satisfaction on the turnover intentions of auditors in the "Big Four" public accounting firms in Indonesia. The study utilized a quantitative research design, where a survey questionnaire was distributed to a sample of auditors working in the firms. The study findings provide important insights into the factors influencing auditors' resignation decisions in Indonesia. The results indicate that work overload and work-related stress have a positive impact on auditors' intention to resign, while job satisfaction has a negative impact. The study recommends that firms should focus on reducing workloads and stress levels and improving job satisfaction to reduce auditor turnover. This can be achieved through better workload management, providing career development opportunities, promoting work-life balance, offering competitive compensation and benefits packages, and creating a positive work environment. These recommendations can inform strategies for retaining and motivating auditors, which can ultimately improve the firm’s operations.